2020
DOI: 10.1001/jamanetworkopen.2020.7559
|View full text |Cite
|
Sign up to set email alerts
|

Association of Neighborhood-Level Disadvantage With Alzheimer Disease Neuropathology

Abstract: IMPORTANCE Social determinants of health, such as income, education, housing quality, and employment, are associated with disparities in Alzheimer disease and health generally, yet these determinants are rarely incorporated within neuropathology research. OBJECTIVE To establish the feasibility of linking neuropathology data to social determinants of health exposures using neighborhood disadvantage metrics (the validated Area Deprivation Index) and to evaluate the association between neighborhood disadvantage a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
122
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(127 citation statements)
references
References 39 publications
(76 reference statements)
5
122
0
Order By: Relevance
“…On average, patients in the teleNP group were residing in geographical neighborhoods with worse metrics on factors including income, education, employment and housing quality. Recent work has found a relationship between higher ADI scores and many outcomes including rates of rehospitalization, cerebral and hippocampal volume, and Alzheimer's disease neuropathology (Hu et al, 2018;Hunt et al, 2020;Powell et al, 2020). Increasing the availability and awareness of teleNP for those most at risk will allow patients to be diagnosed earlier, with important implications for treatment, managing disease progression, and improving quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…On average, patients in the teleNP group were residing in geographical neighborhoods with worse metrics on factors including income, education, employment and housing quality. Recent work has found a relationship between higher ADI scores and many outcomes including rates of rehospitalization, cerebral and hippocampal volume, and Alzheimer's disease neuropathology (Hu et al, 2018;Hunt et al, 2020;Powell et al, 2020). Increasing the availability and awareness of teleNP for those most at risk will allow patients to be diagnosed earlier, with important implications for treatment, managing disease progression, and improving quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Ethno-racial differences may be manifestations of lived experiences in either relative poverty or affluence rather than underlying biological or genetic factors, especially in the context of aging. 51,52 Therefore, gaining an accurate understanding of SES factors is critical in future studies. SES is considered a fundamental social cause of health because greater SES, especially at the neighborhood level, determines the context in which people reside, as well as the resources and risks, such as stress, poverty, and community-level violence, embedded in their context.…”
Section: Discussionmentioning
confidence: 99%
“…31 Addressing these and other disparities in resource-poor environments will require substantial investments to support a more robust set of social and public health interventions. 30,32 Based on the accumulating evidence linking socioeconomically disadvantaged neighborhoods to an increasing number of adverse health outcomes, [1][2][3][4] these investments could potentially lead to cost savings through large-scale reduction of inequalities in morbidity and mortality. 32,33 The outcomes evaluated in the current study, active and disabled life expectancy, are important not only to policy-makers, but also to older persons who consistently identify the maintenance of independent function as their top health outcome priority.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has shown that living in a socioeconomically disadvantaged neighborhood confers increased risk for several adverse outcomes including all-cause mortality, 1 hospital readmission, 2 the incidence and severity of delirium after major surgery, 3 and Alzheimer disease neuropathology. 4 Active and disabled life expectancy, defined as the projected number of remaining years without and with disability in activities of daily living, are often used by policy-makers to forecast the functional well-being of older persons. 5,6 Whether these longitudinal metrics of functional well-being are influenced by neighborhood disadvantage is unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation